2021
DOI: 10.1001/jamanetworkopen.2021.16267
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Insurance Coverage and Cancer Stage at Diagnosis Among Low-Income Adults With Renal Cell Carcinoma After Passage of the Patient Protection and Affordable Care Act

Abstract: IMPORTANCE The association of the Patient Protection and Affordable Care Act (ACA) with insurance status and cancer stage at diagnosis among patients with renal cell carcinoma (RCC) is unknown.OBJECTIVE To test the hypothesis that the ACA may be associated with increased access to care through expansion of insurance, which may vary based on income.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Having health insurance can affect the stage at which ccRCC is diagnosed and therefore the treatments needed. 141 However, individuals with cancer are required to pay a larger proportion of their treatment costs through deductibles and coinsurance, and the costs of RCC treatment have been increasing over time. [142][143][144] Higher patient out-of-pocket costs have been shown to be a barrier to initiating and adhering to recommended cancer treatments.…”
Section: Cost Implicationsmentioning
confidence: 99%
“…Having health insurance can affect the stage at which ccRCC is diagnosed and therefore the treatments needed. 141 However, individuals with cancer are required to pay a larger proportion of their treatment costs through deductibles and coinsurance, and the costs of RCC treatment have been increasing over time. [142][143][144] Higher patient out-of-pocket costs have been shown to be a barrier to initiating and adhering to recommended cancer treatments.…”
Section: Cost Implicationsmentioning
confidence: 99%
“…In the context of RCC, previous studies have shown that possessing health insurance leads to earlier detection, 20 and access to private health insurance is associated with prolonged cancer-specific survival compared to Medicaid insurance. 21 Similarly, we observed higher rates of Medicaid insurance/uninsured among Latinx patients compared to non-Latinx patients (83% vs. 20%, P < .0001).…”
Section: Discussionmentioning
confidence: 99%